National Geographic almanac of American history - Miller, James (National Geographic, 2006)
Featuring National Geographic's hallmark combination of stunning images, superb maps, authoritative narrative, and concise, penetrating analysis, the Almanac of American History has been carefully designed to offer its readers not just a wider and deeper understanding of our country's development, but also an inviting mix of fascinating facts and colorful graphics that make it a browser's delight.